Analisis Jaringan Wireless Local Area Network Menggunakan Parameter Quality Of Service Dan Reliability Maintainability Availability (RMA) - Ester Agung Natanael; Sri Dianing Asri (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Wireless Local Area Network (WLAN) has become an important infrastructure in supporting connectivity in various sectors, but its quality and reliability often experience problems. This study aims to analyze the performance of WLAN networks using two main approaches, namely Quality of Service (QoS) parameters which include throughput, jitter, and packet loss, and the Reliability, Maintainability, and Availability (RMA) method. Tests were conducted before and after network improvements using analysis tools such as Wireshark and iPerf. The results showed that after the repair, throughput increased significantly from an unstable value to an average of 5-5.5 Mbps, jitter decreased consistently, and packet loss reduced from a maximum of 8% to below 2%. In addition, the network availability value increased along with a decrease in repair time (MTTR) and an increase in time between failures (MTBF). This study concludes that the combination of QoS and RMA evaluation provides a comprehensive overview of network performance and reliability, and is effective in supporting decision making for continuous improvement of network systems.